A novel technical route based on wet flue gas desulfurization process for flue gas dehumidification, water and heat recovery. (5th May 2020) - Chen, Zhen; You, Changfu; Wang, Haiming; Xie, Ning
Highlights: A novel technical route was proposed for water and heat recovery in flue gas. A flow pattern controlling device was designed to enhance mass transfer process. The flue gas state at different stage was established by theoretical method. Abstract: To recover the water and heat in industrial flue gas before discharging, a novel dehumidification system was proposed by combining the liquid-desiccant-based dehumidification (LDD) method with the existing wet flue gas desulfurization (WFGD) process in a single spraying tower. Calcium chloride (CaCl2 ) solution was used as a liquid desiccant. A flow pattern controlling (FPC) device was designed to further enhance the mass transfer in the dehumidification process. The effects of liquid-to-gas ratio (L/G), desiccant solution temperature ( Tde ), desiccant concentration ( ω ), and superficial flue gas velocity ( vg ) on the dehumidification performance were investigated. The water and heat recovery process of the LDD-WFGD system were analyzed theoretically in detail. Furthermore, the application potential of the proposed LDD-WFGD system for water and heat recovery for coal-fired power plants was discussed by conducting case studies. The recovered water from flue gas could supply 47.2% and 44.8% of the water demand for the WFGD systems in 660 MW and 330 MW power plants, respectively.